ASSESSMENT OF THE EFFICACY OF TRIAMCINOLONE IN ORABASE AS SYMPTOMATIC TREATMENT OF ORAL LICHEN PLANUS - Durr e Sadaf; Arsalan Wahid; Quratul Ain; Tariq Javed; Saima Chaudhry; Farrukh Imran Mian (Journal of University Medical & Dental College, 2019)
AIM: The aim of this study was to assess the eﬃcacy of topical triamcinolone for the treatment of symptomatic Oral Lichen Planus.MATERIALS AND METHODS: This study was conducted on eligible Oral Lichen Planus patients. 32 patients of symptomatic OLP were enrolled for the study. They were advised to apply an orabase containing 0.1% triamcinolone on lesions 3 times a day for the period of 4 weeks. Follow up visit and intraoral examination of the lesion was performed after completion of 4 weeks.RESULTS: Study was completed by 32 patients. At follow-up examination, orabase containing 0.1% triamcinolone was found to be eﬃcacious in terms of decreasing pain, improving color of the lesion, reducing lesion size and even decreasing the severity and activity of the OLP.CONCLUSION: Orabase containing 0.1% triamcinoloneis eﬀective in treating symptomatic cases of Oral Lichen Planus.